THE EFFECT OF PACKAGING TYPE AND STORAGE TEMPERATURE ON THE SHORT TERM STABILITY OF ELECTROLYTIC CONDUCTIVITY REFERENCE MATERIALS - AYU HINDAYANI; OMAN ZUAS; NURYATINI HAMIM (Journal of Engineering Studies and Research)
In this work, monitoring the effect of packaging type and storage temperature on the short term stability of calibration standard solution KCl 1 M were conducted. The KCl 1M were packaged in two types of packaging i.e., high-density polyethylene (HDPE) and glass bottle. The effects of packaging type and storage temperature were monitored for four weeks at 25 °C and 40 °C. The conductivity values of KCl 1 M in the HDPE and glass bottle were 111.61 mS/cm and 111.62 mS/cm, respectively. The results indicated that the KCl 1M solution at 25 °C in both HDPE and glass bottle were found to be good in short term stability and there was no significant different between the two packaging types. At temperature of 40 °C, however, short term stability of the KCl 1 M in a glass bottle was better than the HDPE bottle.